Women's knowledge about benefits, side effects and complications of combined oral contraceptives: cross-sectional study (Revista Científica Integrada, 2024)
Objective: To associate women's knowledge about the benefits, side effects and complications related to the use of oral contraceptives combined with socioeconomic variables, coitarca and professional guidance on the method. Methods: Analytical, cross-sectional, quantitative study, developed between December 2022 and February 2023, with 150 women of childbearing age, who used combined oral contraceptives (COC), in a health institution linked to Primary Health Care, located in a city in the interior of Piauí. A semi- structured form was applied in the collection. The data was entered and analyzed in the Statistical Package for the Social Sciences. There was approval from the Research Ethics Committee. Results: Of the interviewees, 82 (54.7%) were up to 29 years old; 126 (84.0%) were black; 51 (34.0%), students; 83 (55.3%), without a partner; 141 (94.0%), with religion; 106 (70.7%), income of up to one minimum wage; and 128 (85.3%), occupation. 83 (55.3%) had coitarca after the age of 17; 91 (60.7%) had become pregnant; and 119 (79.3%) received professional guidance on COC. There was a statistically significant association between family income and knowledge of COC benefits (p
Keywords: Women's Health; Knowledge; Combined Oral Contraceptives; Sexual and Reproductive Health